Effects of a mouthwash with chlorine dioxide on oral malodor and salivary bacteria: a randomized placebo-controlled 7-day trial - Shinada, Kayoko; Ueno, Masayuki; Konishi, Chisato; Takehara, Sachiko; Yokoyama, Sayaka; Zaitsu, Takashi; Ohnuki, Mari; Wright, Fredrick Allan Clive; Kawaguchi, Yoko (Current controlled trials in cardiovascular medicine, 2010)
Background Previous research has shown the oxidizing properties and microbiological efficacies of chlorine dioxide (ClO 2 ). Its clinical efficacies on oral malodor have been evaluated and reported only in short duration trials, moreover, no clinical studies have investigated its microbiological efficacies on periodontal and malodorous bacteria. Thus, the aim of this study was to assess the inhibitory effects of a mouthwash containing ClO 2 used for 7 days on morning oral malodor and on salivary periodontal and malodorous bacteria. Methods/Design A randomized, double blind, crossover, placebo-controlled trial was conducted among 15 healthy male volunteers, who were divided into 2 groups. Subjects were instructed to rinse with the experimental mouthwash containing ClO 2 or the placebo mouthwash, without ClO 2 , twice per day for 7 days. After a one week washout period, each group then used the opposite mouthwash for 7 days. At baseline and after 7 days, oral malodor was evaluated with Organoleptic measurement (OM), and analyzed the concentrations of hydrogen sulfide (H 2 S), methyl mercaptan (CH 3 SH) and dimethyl sulfide ((CH 3 ) 2 S), the main VSCs of human oral malodor, were assessed by gas chromatography (GC). Clinical outcome variables included plaque and gingival indices, and tongue coating index. The samples of saliva were microbiologically investigated. Quantitative and qualitative analyses were performed using the polymerase chain reaction-Invader method. Results and Discussion The baseline oral condition in healthy subjects in the 2 groups did not differ significantly. After rinsing with the mouthwash containing ClO 2 for 7 days, morning bad breath decreased as measured by the OM and reduced the concentrations of H 2 S, CH 3 SH and (CH 3 ) 2 S measured by GC, were found. Moreover ClO 2 mouthwash used over a 7-day period appeared effective in reducing plaque, tongue coating accumulation and the counts of Fusobacterium nucleatum in saliva. Future research is needed to examine long-term effects, as well as effects on periodontal diseases and plaque accumulation in a well-defined sample of halitosis patients and broader population samples. Trial registration ClinicalTrials.gov NCT00748943